2021
DOI: 10.1016/j.celrep.2021.109866
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and phosphoproteomic analyses identify liver-related signaling in retinal pigment epithelial cells during EMT

Abstract: Epithelial-mesenchymal transition (EMT) of the retinal pigment epithelium (RPE) is associated with several blinding retinal diseases. Using proteomics and phosphoproteomics studies of human induced pluripotent stem cell-derived RPE monolayers with induced EMT, we capture kinase/phosphatase signaling cascades 1 h and 12 h after induction to better understand the pathways mediating RPE EMT. Induction by co-treatment with transforming growth factor b and tumor necrosis factor alpha (TGNF) or enzymatic dissociatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 94 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Given the role of RPE–EMT in PVR and possibly in AMD, efforts have been made to identify inhibitors of RPE–EMT for potential therapeutic use [ 44 , 45 ]. Despite some progress in this field [ 46 , 47 ], since a safe and effective RPE–EMT inhibitor has yet to be reported, we sought to utilize our previously reported RPE–EMT model and transcriptional studies [ 10 , 11 , 12 ] to identify a suitable inhibitor. Our previous transcriptomic [ 11 ], proteomic [ 10 ], and phosphoproteomic [ 12 ] studies identified several malignancy-associated EMT factors that were also significantly altered during RPE–EMT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the role of RPE–EMT in PVR and possibly in AMD, efforts have been made to identify inhibitors of RPE–EMT for potential therapeutic use [ 44 , 45 ]. Despite some progress in this field [ 46 , 47 ], since a safe and effective RPE–EMT inhibitor has yet to be reported, we sought to utilize our previously reported RPE–EMT model and transcriptional studies [ 10 , 11 , 12 ] to identify a suitable inhibitor. Our previous transcriptomic [ 11 ], proteomic [ 10 ], and phosphoproteomic [ 12 ] studies identified several malignancy-associated EMT factors that were also significantly altered during RPE–EMT.…”
Section: Resultsmentioning
confidence: 99%
“…Despite some progress in this field [ 46 , 47 ], since a safe and effective RPE–EMT inhibitor has yet to be reported, we sought to utilize our previously reported RPE–EMT model and transcriptional studies [ 10 , 11 , 12 ] to identify a suitable inhibitor. Our previous transcriptomic [ 11 ], proteomic [ 10 ], and phosphoproteomic [ 12 ] studies identified several malignancy-associated EMT factors that were also significantly altered during RPE–EMT. Although malignancy-associated EMT is controlled by a variety of biological pathways, NF-κB signaling is activated in a wide range of human cancers, and is involved in maintaining epithelial cell plasticity and metastasis via the orchestrated modulation of IKK-2/IκBα/NF-κB [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of endothelial-mesenchymal transition induction on the RPE layer derived from human induced pluripotent stem cells, it was found that the HGF-MET signal showed the highest overall enrichment. In addition, they also found that HGF signaling plays a role in regulating the transcription profile of RPE (Mertz et al, 2021).Thus, it will be intriguing to study whether altered expression of HGF in liver diseases could exsert distance influence on ocular condition.…”
Section: Hepatocyte Growth Factormentioning
confidence: 99%